Analisis Kesalahan Sintaksis pada Teks Berita Daring berjudul Mencari Etika Elite Politik di saat Covid-19 - Ade Dufadhol Ariyadi; Asep Purwo Yudi Utomo (Jurnal Bahasa dan Sastra, 2020)
This research is motivated by the frequent finding of various errors in Indonesian in online news writing. The most obvious mistakes are at the syntactic level. Therefore, this study aims to describe and explain the form of language errors in the syntax field contained in the Kompasiana online news portal in the text entitled Mencari Etika Elite Politik di saat Covid-19. This research applies qualitative methods with a descriptive approach. To obtain data, the observation technique was chosen as the data collection method. This is done through observing the use of language and note-taking techniques to record the structures being analyzed. Furthermore, the data were analyzed using distributional methods. The results of the research regarding the analysis of language errors in the syntactic field contained in the article include non-standard structured sentence errors, coherence, loanwords used in sentences, unity and logic of sentences, sentence effectiveness. This finding further strengthens the paradigm that online news text writing often ignores Indonesian syntactic principles.